2018
DOI: 10.4081/mrm.2018.191
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors, and impact of lung cancer on outcomes of idiopathic pulmonary fibrosis: a study from the Middle East

Abstract: Background: No studies have addressed the impact of lung cancer (LC) on prognosis of patients with idiopathic pulmonary fibrosis (IPF) in Upper Egypt. We aimed to evaluate the prevalence and risk factors for LC among IPF patients and its impact on their outcomes and survival in Upper Egypt. Methods: A total of 246 patients with IPF who had complete clinical and follow up data were reviewed. They were categorized into 2 groups: 34 patients with biopsy-proven LC and IPF (LC-IPF) and 212 patients with IPF o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…The incidence of LC in patients who had been hospitalized with pneumonia was significantly higher than in the general population [28]. This is expected to be more challenging in patients with LC-IPF [2], particularly those who receive chemo-or radiotherapy for their disease [2,4]. The use of sensitive biomarkers, like PCT, could be helpful in that situation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of LC in patients who had been hospitalized with pneumonia was significantly higher than in the general population [28]. This is expected to be more challenging in patients with LC-IPF [2], particularly those who receive chemo-or radiotherapy for their disease [2,4]. The use of sensitive biomarkers, like PCT, could be helpful in that situation.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic search of the patient database at the chest department of AUH revealed that 152 patients fulfilled the international guidelines on the diagnosis and management of IPF [1] during the period of August 1, 2014, to August 31, 2019. Among these 152 patients, we randomly selected 137 patients diagnosed with IPF who were then followed up regularly at our department according to a prospective protocol for the follow-up of IPF patients, as shown previously [2]. The remaining 15 patients were excluded due to incomplete follow-up data.…”
Section: Study Design and Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, LC also has high incidence and mortality, and men's morbidity and mortality are more than twice than that of women (6). Most studies suggested that the occurrence of LC is related to environmental (smoke, occupational exposure, and air pollution) and genetic factors (7,8), especially genetic factors play important role. Li et al (9) revealed that LC susceptibility in Chinese Han population is related to HOTAIR gene mutation.…”
Section: Introductionmentioning
confidence: 99%
“…At present, surgery is still the treatment of choice for early stage lung cancer, most lung cancer patients have been diagnosed at an advanced stage, lost the best treatment opportunity, and its 5-year survival rate is only 19.7% [1,3]. Most studies suggested that the occurrence of Lung cancer is related to environmental, such as smoking, occupational exposure, and air pollution [4,5]. At the same, genetic factors play an important role in the development of lung cancer, including EGFR [6], CHRNA5 [7], CLPTM1L [8], TP63 [9], and so on.…”
Section: Introductionmentioning
confidence: 99%